Spatial accounting methods and the construction of spatial Social Accounting Matrices - Bjarne Madsen; Chris Jensen-Butler (European Regional Science Association (ERSA), 2005)
The paper examines adaptations to regional accounts used to construct regional and interregional Social Accounting Matrices (SAMs). Balancing procedures for commodities and factors are transferred from National to Regional accounts and procedures to construct spatial data on interaction are also included in the data-building process. Both involve a novel approach using the geographical concepts of place of production for production activities, place of residence for institutions, market place for commodities and market place for factors. The use of these concepts permits accounting balances to be calculated at the spatial level. It is argued that as the size of basic areal unit used in studies declines, more traditional accounting approaches are no longer satisfactory. The theoretical basis of the spatial regional accounting model is presented and an example of the construction of a Danish Interregional SAM (SAM-K) is examined, where particular attention is given to data requirements, showing that these are much more modest than generally assumed.
Keywords: 330